El barómetro y los proyectos meteorológicos de la Ilustración: el caso español - Guijarro Mora, Víctor (ENDOXA, 2005)
In Spain, apart from popular uses, the barometer was concicved in the IS'*" Century to supply cuantitative observations in order to establish climatic parameters. These projects were supported by a dominant utilitarian mentality: after the examination of data it was supposed that relevant conclusions could be obtained for the knowledge of healthy environmental conditions as well as for the improvement of agricultural skills. This, in turn, focused the attention on a type of barometer in which reliability, and not extreme precisión, was the priority.